2000
DOI: 10.1192/bjp.176.4.369
|View full text |Cite
|
Sign up to set email alerts
|

Labour and delivery complications at birth and later mania

Abstract: These findings suggest that obstetric adversity is not a risk factor for later mania.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…Mental health risks to women include the occurrence of mood episodes during pregnancy, rates of which varied across the studies from 9 to 18 %. Mood episodes were more common in the postpartum period [73, 75], ranging from 25 to 79 %, with differences possibly due to small sample sizes in some studies [36, 44]. It has been suggested that this may be due to placental hormones increasing throughout pregnancy, and their abrupt cessation after birth [75].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mental health risks to women include the occurrence of mood episodes during pregnancy, rates of which varied across the studies from 9 to 18 %. Mood episodes were more common in the postpartum period [73, 75], ranging from 25 to 79 %, with differences possibly due to small sample sizes in some studies [36, 44]. It has been suggested that this may be due to placental hormones increasing throughout pregnancy, and their abrupt cessation after birth [75].…”
Section: Discussionmentioning
confidence: 99%
“…1). Reasons for exclusion were: drug related issues (21 papers, [14, 18–37]), no focus on the chosen study group (six papers, [3843]), outcomes in women not diagnosed before pregnancy (two papers, [44, 45]), mixed groups bipolar disorder and schizophrenia (two papers, [46, 47]), discussion paper (two papers, [48, 49]), gender mixed groups also including men (one paper, [50]), duplicates (one paper, [15]). Occasionally it was difficult to separate the different diagnoses that were included in the sample; for example, in Doyle et al [46] it was not possible to find separate data for the three included groups: BD I, BD II and schizoaffective disorders bipolar type.…”
Section: Methodsmentioning
confidence: 99%
“…This genetic architecture was predicted by the elevated rates of bipolar disorder, unipolar depression, and psychosis in first-degree relatives of bipolar patients (Gershon et al, 1982). Compared with schizophrenia, there is weaker evidence for presumed environmental aetiologies such as obstetric complications or inner city residence (I, (Bain et al, 2000; Browne et al, 2000; Lloyd and Jones, 2002)).…”
Section: Part 2 Consensus Points and Review Fundamentals Of Patient mentioning
confidence: 99%
“…All except one study [Lewis and Murray, 1987] have been carried in small samples, and obstetrical history has been retrospectively obtained through maternal recall. A recent study using obstetrical records of 76 subjects with bipolar disorder and of 76 normal controls matched for year and maternity of birth did not find an excess of OCs in subjects with bipolar disorder [Browne et al, 2000]. No population‐based or cohort study has specifically investigated the link between OCs and bipolar disorder.…”
Section: What Is the Diagnostic Specificity Of The Association Betweementioning
confidence: 99%